Cognitive dysfunction and white matter hyperintensities in Fabry disease. Issue 4 (2nd April 2022) - Murphy, Patrick; Williams, Fay; Davagnanam, Indran; Chan, Edgar; Murphy, Elaine; Hughes, Derralynn; Quattrocchi, Gabriella; Werring, David J.; Lachman, Robin H.; Cipolotti, Lisa
Abstract: Fabry disease (FD) is an X‐linked lysosomal storage disorder with multi‐system involvement including cerebrovascular disease. Patients with FD also have a high risk of ischaemic stroke and TIA. White matter hyperintensities are common, but their clinical impact on cognition remains uncertain. Previous studies have examined the neuropsychological profile of FD, but have been inconclusive in part due to methodological limitations including small sample sizes. We sought to address these limitations in a case‐control study of 26 patients with Fabry disease with mild to moderate disease symptoms matched with 18 healthy controls for age and premorbid intellectual level. We obtained detailed neuropsychological data and MRI neuroimaging data on the severity of white matter changes. Mood was accounted for as a possible confounder. Our results showed significant compromise of executive functions and information processing speed for the FD group. Error analyses suggested that the compromise of executive functions could not be entirely accounted for by slowed information processing speed. We demonstrated significant correlations between cognitive decline and the overall volume of white matter hyperintensities in the FD group. Our results point to significant compromise of cognition in FD even without stroke or mood difficulties. This suggests that neuropsychological assessment and rehabilitation should be routinely offered to patients with FD.